THE CONCEPT AND NOTION OF PROFESSIONAL LIABILITY INSURANCE - Baklachyan, Davit (State and Law, 2023)
The article attempts to identify the most significant problems of professional liability insurance at the present time and ways to overcome them in order to form an independent type of liability insurance. The need to introduce general norms of professional liability insurance is justified by the differences of such a contract with insurance contracts of contractual and tort liability, as a complex, having features in the subject composition, insurable interest, insurance risk of the contract.